Robust Radio Direction Finding System Using Nested Antenna Array Based on Total Forward – Backward Matrix Pencil Algorithm - Han, Trong Thanh; Nguyen, Duc Moi; Vu, Van Yem (Old Journal, 2018)
The performance of radio direction finding systems mainly depends on kind of antenna array and signal processing algorithms. In this paper, a Robust radio direction finding system using Nested Antenna Array (NAA) based on Total Forward – Backward Matrix Pencil (TFBMP) method is proposed. By inheriting advantages of both NAA and TFPMP. Therefore, the proposed system can estimate more number of incoming signals than the number of antenna element with only one snapshot. This mean that system size and the sampling frequency in real time receivers can be considerably reduced. The simulation results for DOA estimation using proposed system will be assessed and analyzed to verify its performance.